The Limits of Computer Science. Weizsäcker’s Argument - Olszewski Adam (Studies in Logic, Grammar and Rhetoric)
The main purpose of this paper, which takes the form of an essay, is an attempt to answer the question of the limits of artificial intelligence (AI). In the introductory section, we present the key milestones in AI development, both historical and future projections, in which two terms – Artificial Human (AH) and Artificial ‘god’ (AG) – play a special role. In the second section, we clarify the question of the limits of AI by indicating the hypothetical goal of AI development. The third section develops the argument proposed by C. F. Weizsäcker, originally formulated for cybernetics. The conclusion of this argument is optimistic about limitations to the possibilities of cybernetic simulations. We apply this argument to AI and subject it to a critique which ultimately undermines the legitimacy of its conclusion. We base the critique on two well-known results: the theorem of the unsolvability of the halting problem and Gödel’s first incompleteness theorem, and we formulate two objections interpreted without adopting Church’s thesis. In the crucial fourth section, we present a third objection in the form of a hypothesis for which we argue that AI (AH), understood as a subject, will always be solipsistic.